2002
DOI: 10.1152/ajpregu.00771.2000
|View full text |Cite
|
Sign up to set email alerts
|

Loss of circadian organization of sleep and wakefulness during hibernation

Abstract: [851][852][853][854][855][856][857][858] 1997]. Animals maintained under constant conditions continued to display circadian rhythms in both sigma activity and brain temperature throughout euthermic intervals, whereas sleep and wakefulness showed no circadian organization. Instead, sleep and wakefulness were distributed according to a 6-h ultradian rhythm. SWA, NREM sleep bout length, and sigma activity responded homeostatically to the ultradian sleep-wake pattern. We suggest that the loss of sleep-wake consoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 56 publications
0
13
1
Order By: Relevance
“…The persistence and potential function of circadian oscillators during hibernation is contentious (reviewed in Larkin et al 2002). Very low-amplitude (0.1Њ-0.2ЊC) circadian T b rhythms with a broad range of period lengths have been detected during deep torpor in hibernators held under constant dark in captive conditions (Grahn et al 1994;Florant et al 2000;Larkin et al 2002;Ruby et al 2002), whereas others have failed to detect persistent rhythms in either captive or free-living animals (Florant et al 2000;Hut et al 2002;Gür et al 2009;Tøien et al 2011;Williams et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence and potential function of circadian oscillators during hibernation is contentious (reviewed in Larkin et al 2002). Very low-amplitude (0.1Њ-0.2ЊC) circadian T b rhythms with a broad range of period lengths have been detected during deep torpor in hibernators held under constant dark in captive conditions (Grahn et al 1994;Florant et al 2000;Larkin et al 2002;Ruby et al 2002), whereas others have failed to detect persistent rhythms in either captive or free-living animals (Florant et al 2000;Hut et al 2002;Gür et al 2009;Tøien et al 2011;Williams et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Very low-amplitude (0.1Њ-0.2ЊC) circadian T b rhythms with a broad range of period lengths have been detected during deep torpor in hibernators held under constant dark in captive conditions (Grahn et al 1994;Florant et al 2000;Larkin et al 2002;Ruby et al 2002), whereas others have failed to detect persistent rhythms in either captive or free-living animals (Florant et al 2000;Hut et al 2002;Gür et al 2009;Tøien et al 2011;Williams et al 2012). Florant et al (2000) found that T b rhythms were due to oscillations in T a within the chamber, whereas Ruby et al (2002) concluded that the T b oscillations were independent of T a .…”
Section: Discussionmentioning
confidence: 99%
“…Brains in organisms such as mice, bats, and ground squirrels can drop below 25°C during bouts of torpor or hibernation and may still express circadian rhythms in body temperature (Hut et al 2002;Ruby et al 2002). Recently, Larkin et al (2002) provided compelling evidence that the circadian regulation of brain temperature continues, albeit at much reduced amplitude, in the hibernating squirrel SCN at ambient temperatures as low as 9°C. These animals, however, lost their circadian rhythm in slow-wave sleep.…”
Section: Discussionmentioning
confidence: 99%
“…SWA was normalized to the 24-h mean NREMS SWA in baseline for each animal. NREMS bouts were calculated according to previously published criteria (27). In short, an NREMS bout started with a first 10-s epoch scored as NREMS and lasted until three consecutive 10-s epochs of either wakefulness or REM sleep were encountered.…”
Section: Methodsmentioning
confidence: 99%